The adverse impact of excessive internet use during the COVID-19 pandemic on adolescents' coping skills: A case study in Hanoi, Vietnam 2021 - Quyen Thi Tu Bui; Chi Thi Lan Pham; Anh Ha Le; Duy Quang Pham (Frontiers Media S.A., 2022)
IntroductionThe COVID-19 pandemic has created significant stressors in Vietnamese adolescents' lives. Coping skills play important roles in helping adolescents contend with stress. This study aimed to evaluate adolescents' coping skills during the COVID-19 pandemic and examine how those skills are impacted by excessive internet use during this pandemic.MethodsThe study used respondent-driven sampling and Google online survey forms to collect data. The study sample included 5,315 high school students aged 11- 17 years in Hanoi's rural and urban areas. The Kid Coping Scale was applied to examine adolescents' coping, and the coping score was compared among adolescents with different levels of internet use.ResultsThe average coping score measured by Kid Coping Scale was 20.40 (std = 2.13). About half of adolescents often "avoid the problem or the area where it happened" when experiencing a hard time. One-third of adolescents often stopped thinking about the problem they faced. More than one-fourth of respondents stayed online for at least 8 h per day. The online time for learning/other activities showed a reverse dose-response relationship with the coping score; the longer the internet use duration, the lower the coping score.ConclusionThe mean score of coping of Hanoi adolescents was moderate. Internet use has an adverse impact on their coping skills.